Hypertension as a social and spiritual experience: A qualitative study in Paccellekang Village, Indonesia (Al-Sihah : The Public Health Science Journal, 2025)
Although hypertension is widely addressed in clinical literature, limited attention has been given to its social and spiritual dimensions, particularly in rural settings. This study explores the lived experiences of individuals with hypertension in Paccellekang Village, South Sulawesi, Indonesia, aiming to understand how they perceive and cope with the condition. A qualitative phenomenological design was employed, involving in-depth interviews with seven hypertensive participants from March to May 2025. Thematic analysis using Colaizzi’s method revealed four main themes: personal experience of emotional distress and physical limitation; the meaning of hypertension as both an illness and a divine test; the role of spirituality and family support in managing the condition; and adaptive strategies involving lifestyle changes and informal health knowledge. These highlight that hypertension is perceived as a multidimensional experience shaped by culture, beliefs, and social relationships. The study emphasizes the need for culturally sensitive and spiritually integrated interventions in rural communities to improve adherence and promote holistic well-being. This contributes directly to strengthening primary healthcare initiatives in rural Indonesia. The study concludes that effective hypertension care in rural communities must consider these social and spiritual dimensions. It is recommended that health education programs integrate religious values and community-based support to strengthen treatment adherence and improve patient well-being.